2020
DOI: 10.1364/osac.384607
|View full text |Cite
|
Sign up to set email alerts
|

Generation of highly efficient terahertz radiation in ferromagnetic heterostructures and its application in spintronic terahertz emission microscopy (STEM)

Abstract: The laser terahertz emission microscopy (LTEM) technique, which breaks through the resolution limitation of terahertz waves from millimeter to micrometer scales, has been widely used in many real application circumstances, such as contactless chip nondestructive testing, biosensing, imaging, and so on. Recently developed spintronic terahertz emitters featuring many unique properties such as high efficiency, easy integration, low cost, large size and so on, may also have great applications in LTEM, which can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…With the rapid progress in these years, the spintronic THz emitters have already manifested their advantages of high efficiency, ultrabroadband, and low cost, and been used in ghost microscope imaging and integrated on‐chip biosensing applications. [ 22–25 ] Though the competitive spintronic THz emitters have many merits, the intrinsic spin‐to‐charge conversion (SCC) mechanism impedes the production of elliptically polarized THz waves. [ 17 ] The reported elliptically or circularly polarized THz waves from spintronic THz emitters were produced either by delicately engineering the magnetization vector directions [ 12 ] or using cascading emission method.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid progress in these years, the spintronic THz emitters have already manifested their advantages of high efficiency, ultrabroadband, and low cost, and been used in ghost microscope imaging and integrated on‐chip biosensing applications. [ 22–25 ] Though the competitive spintronic THz emitters have many merits, the intrinsic spin‐to‐charge conversion (SCC) mechanism impedes the production of elliptically polarized THz waves. [ 17 ] The reported elliptically or circularly polarized THz waves from spintronic THz emitters were produced either by delicately engineering the magnetization vector directions [ 12 ] or using cascading emission method.…”
Section: Introductionmentioning
confidence: 99%
“…Arrays of W/Fe/Pt were proposed to form a THz near-field microscope capable of illuminating an object at an extreme near field [55]. Guo et al [56] examined the possibility to integrate W/CoFeB/Pt heterostructures in laser terahertz emission microscopy (LTEM) technique. Müller et al [57] have demonstrated efficient coupling of THz-pulses emitted from W/CoFeB/Pt trilayer to the junction of a scanning tunneling microscope, that has the potential to enable spatiotemporal imaging with femtosecond temporal and sub-nm spatial resolution.…”
Section: Future Perspectives Of Thz Spintronic Emittersmentioning
confidence: 99%
“…Nakajima [17] has reviewed the progress of laser driven electron beam and radiation sources and mentioned their various applications. If we focus on the very recent research, we find remarkable work on THz radiation using crystals [18], metal-dielectric layers [19], medium containing nanoparticles [20] and ferromagnetic heterostructures [21]. In optical rectification technique, this has been experimentally shown that the emitted THz radiation depends on the crystal orientation and excitation polarization in the case of BaGa 4 Se 7 crystal [18].…”
Section: Introductionmentioning
confidence: 99%
“…Considering a metal in contact with a nanolayer of dielectric, femtosecond lasers are found to generate THz radiation in dielectric-metal structure, where the field can be enhanced due to interference of incident and reflected waves in the dielectric [19]. The oblique incidence of a femtosecond laser on W/CoFeB/Pt trilayer heterostructures has shown to scale up the stable THz emission if one uses the remnant magnetization and this can have application in Spintronic Terahertz Emission Microscopy (STEM) in view of its high performance [21]. On the other hand, it has been shown that the emitted THz radiation can be tuned with respect to its power and focus by manipulating the shape and orientation of nanoparticles embedded in a gaseous medium [20].…”
Section: Introductionmentioning
confidence: 99%